Possible association between Mycobacterium paratuberculosis infection and Crohn's disease in human - DIMARELI-MALLI (Ζ. ΔΗΜΑΡΕΛΛΗ-ΜΑΛΛΗ), Z.; SARRIS (Κ. ΣΑΡΡΗΣ), C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Crohn's disease is a granulomatous ileocolitis of humans, of unknown aetiology, which generally manifests itself during the prime of life. The chronic, progressive clinical course and histological findings are consistent wiht a mycobacterial aetiology. Evidence supporting a pathogenic role for a mycobacterium has become available only in the last decade with the isolation of this microorganism from Crohn's disease tissue. M. paratuberculosis, which is the causative agent of Johne's disease in animals, has been identified in patients with Crohn's disease by PCR and DNA hybridisation techniques. It has been shown that isolates of M. paratuberculosis from Crohn's disease are indentical with pathogenic strains in ruminants.